2022
DOI: 10.3389/fnsyn.2022.858340
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic Mitochondria Communicate With Release Sites for Spatio-Temporal Regulation of Exocytosis at the Motor Nerve Terminal

Abstract: Presynaptic Ca2+ regulation is critical for accurate neurotransmitter release, vesicle reloading of release sites, and plastic changes in response to electrical activity. One of the main players in the regulation of cytosolic Ca2+ in nerve terminals is mitochondria, which control the size and spread of the Ca2+ wave during sustained electrical activity. However, the role of mitochondria in Ca2+ signaling during high-frequency short bursts of action potentials (APs) is not well known. Here, we studied spatial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 82 publications
(125 reference statements)
0
8
0
Order By: Relevance
“…Disruption to this system has been shown to impact the RP but not the RRP [52]. Mitochondria have also been shown to contribute to releasing and replenishing the RRP; however, whether that mechanism relies on its ability to regulate calcium or to produce ATP, or a combination of the two, is not yet understood [56].…”
Section: Mitochondrial Atp Production At the Presynapsementioning
confidence: 99%
“…Disruption to this system has been shown to impact the RP but not the RRP [52]. Mitochondria have also been shown to contribute to releasing and replenishing the RRP; however, whether that mechanism relies on its ability to regulate calcium or to produce ATP, or a combination of the two, is not yet understood [56].…”
Section: Mitochondrial Atp Production At the Presynapsementioning
confidence: 99%
“…Since the electrophysiological response to nifedipine during high-frequency stimulation in immature control terminals (Figure 4A,B) recalls the increased and reliable response in adult mice [36,40], we explored whether nifedipine was still able to enhance evoked and spontaneous secretion in adult mice. We found that the average quantal releases during trains of 0.5-20 Hz were indistinguishable with or without nifedipine (Figure 5A,B).…”
Section: The Rrp Pool Size Is Insensitive To Nifedipine In Adult Moto...mentioning
confidence: 99%
“…Since nifedipine positively modulates synaptic strength by increasing the RRP (Figure 4), which indicates enhanced vesicle priming, we explored whether the Ca 2+ -CaM complex participates in this response. Modulation of priming is a Ca 2+ -dependent process that may affect the RRP effective size [40], vesicle refilling rate during repetitive stimulation, or both. Indeed, it has been shown that CaM plays a role in replenishing synaptic vesicles during high-frequency repetitive stimulation [41,42].…”
Section: The Effect Of Nifedipine On the Rrp Is Calmodulin-independentmentioning
confidence: 99%
“…As neurons are extensively polarized and subspecialized cells, newly generated mitochondria undergo anterograde active transport to ensure energy supply in all compartments, while retrograde transport moves damaged mitochondria back to the soma [42]. In developing neurons, mitochondria are concentrated at growth cones and axonal branching sites; in mature neurons, mitochondria form functional domains-upon anchoring to actin cytoskeleton and microtubules-at pre-and post-synapses [43][44][45]. This distribution of mitochondria allows local Ca 2+ buffering and ATP production to sustain local translation, actin dynamics, and finely regulate vesicles fusion/replenishment during firing [43][44][45].…”
Section: Role Of Mitochondria In Neuronsmentioning
confidence: 99%
“…In developing neurons, mitochondria are concentrated at growth cones and axonal branching sites; in mature neurons, mitochondria form functional domains-upon anchoring to actin cytoskeleton and microtubules-at pre-and post-synapses [43][44][45]. This distribution of mitochondria allows local Ca 2+ buffering and ATP production to sustain local translation, actin dynamics, and finely regulate vesicles fusion/replenishment during firing [43][44][45]. At the same time, local protein synthesis of nuclear-encoded mitochondrial genes occurs in axons, and it is crucial to maintain mitochondria morphology and membrane potential [46][47][48].…”
Section: Role Of Mitochondria In Neuronsmentioning
confidence: 99%